Analisis Kesulitan dalam Mendeklamasikan Puisi pada Siswa Kelas VIII SMP Negeri 1 Mempawah Hulu - Syahrul, Syahrul; Fitriani, Fitriani; Alimin, Al Ashadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Aims to describe the types of difficulties, contributing factors, and solutions in poetry declamation among eighth-grade students of class VIII C at SMP Negeri 1 Mempawah Hulu. The study employed a qualitative approach using a descriptive method with a single instrumental case study design. Data were collected through observation, interviews, questionnaires, and documentation. Data analysis involved data reduction, data display, and conclusion drawing, while data validity was ensured through technique and source triangulation. The findings reveal that students’ difficulties in poetry declamation include unclear articulation, monotonous intonation, rigid expressions and gestures, and insufficient internalization of the poem’s meaning. These difficulties are influenced by internal and external factors. Internal factors include low self-confidence, performance anxiety, limited understanding of the poem’s meaning, and insufficiently trained vocal skills. External factors include less varied teaching methods, a lack of appropriate declamation models, limited practice opportunities, an unsupportive learning environment, and limited facilities for literature learning. The solutions implemented include continuous declamation practice, the use of more engaging teaching methods and learning media, the provision of appropriate declamation examples, and teacher guidance to enhance students’ self-confidence. This study is expected to serve as a reference for improving the quality of poetry declamation instruction at the junior high school level.